Plastic poems: literature and image in the work of two contemporary Latin American poets of Asian inspiratio - Fernández Bravo , Álvaro (Letras, 2024)
This article explores the relationship between poetry and image in the work of two Argentine poets, Hugo Padeletti and Liliana Ponce. The work of both poets allows us to examine the dialogue between verbal language and visual art and opens a set of questions around the transcription of visual forms in poems, as an operation that differs from translation. It is possible to recognize aspects of the temporal dimension of the Buddhist cosmogony in the texts and images addressed.